Modelo de Análise e Prevenção de Acidentes - MAPA: ferramenta para a vigilância em Saúde do trabalhador - Almeida, Ildeberto Muniz de [UNESP]; Vilela, Rodolfo Andrade De Gouveia; Silva, Alessandro José Nunes Da; Beltran, Sandra Lorena (ABRASCO - Associação Brasileira de Saúde Coletiva, 2014)
The analysis of work-related accidents is important for accident surveillance and prevention. Current methods of analysis seek to overcome reductionist views that see these occurrences as simple events explained by operator error. The objective of this paper is to analyze the Model of Analysis and Prevention of Accidents (MAPA) and its use in monitoring interventions, duly highlighting aspects experienced in the use of the tool. The descriptive analytical method was used, introducing the steps of the model. To illustrate contributions and or difficulties, cases where the tool was used in the context of service were selected. MAPA integrates theoretical approaches that have already been tried in studies of accidents by providing useful conceptual support from the data collection stage until conclusion and intervention stages. Besides revealing weaknesses of the traditional approach, it helps identify organizational determinants, such as management failings, system design and safety management involved in the accident. The main challenges lie in the grasp of concepts by users, in exploring organizational aspects upstream in the chain of decisions or at higher levels of the hierarchy, as well as the intervention to change the determinants of these events.

A análise de acidentes de trabalho é importante para a vigilância e a prevenção desses eventos. Métodos atuais de análise buscam superar visões reducionistas que enxergam essas ocorrências como eventos simples explicados por erros dos operadores. O objetivo do artigo é analisar o modelo de análise e prevenção de acidentes (MAPA) e seu uso em intervenções de vigilância, destacando aspectos vivenciados na apropriação da ferramenta. Optou-se por método descritivo analítico apresentando as etapas do modelo. Para ilustrar contribuições e ou dificuldades foram selecionados casos nos quais foi usada a ferramenta em contexto de serviço. O MAPA integra abordagens teóricas já experimentadas em estudos de acidentes fornecendo apoio conceitual útil desde a etapa de coleta de dados à conclusão e intervenção. Além de revelar fragilidades da abordagem tradicional, ajuda a identificar determinantes organizacionais como falhas gerenciais, de concepção de sistemas e da gestão de segurança envolvidas na acidentalidade. Os principais desafios encontram-se no domínio dos conceitos pelos usuários, na exploração de aspectos organizacionais mais à montante na cadeia de decisões ou em níveis superiores da hierarquia, bem como na intervenção para mudanças nos determinantes destes eventos.
Model of Analysis and Prevention of Accidents - MAPA: tool for operational health surveillance
Keywords: Acidente de trabalho; Método de análise; Vigilância e prevenção; Saúde do trabalhador; Work-related accident; Method of analysis; Surveillance and prevention; Operational health